Preparation and characterization of urea-formaldehyde-pepsin bioconjugate: a new biocatalyst system - Vinod, V. P.; Shinde, Sudhirkumar; D'Britto, Virginia; Shukla, P. G.; Rao, Mala (Biotechnology Progress, 2006)
This study describes the synthesis of urea formaldehyde (UF) microspheres by a dispersion polycondensation polymerization method. These microspheres with proper F/U molar ratio can provide highly reactive groups, capable of further condensation with the amino acid residues of enzyme/proteins. Presence of methylols groups in UF microspheres was confirmed by C-13 NMR study. Pepsin, a proteolytic enzyme, was immobilized on the UF microspheres to form bioconjugate system. As compared to the free enzyme in solution, the pepsin in the bioconjugate system exhibited significantly enhanced pH and temperature stability. The urea-formaldehydepepsin bioconjugate system also exhibited excellent proteolytic activity over eight successive reuse cycles with more than 50% of initial activity. A highlight of this new biocatalyst is the ease with which separation of this biocatalyst from the reaction medium may be achieved by mild centrifugation.

pH Induced structural alterations in an aspartic protease from Vigna radiata indicating an alkali induced molten globule state - Kulkarni, Aarohi; Gaikwad, Sushama M.; Rao, Mala (International Journal of Biological Macromolecules, 2008)
pH-dependent transitions in secondary and tertiary structure are described for a plant aspartic protease from Vigna radiata. The enzyme was pH stable with pH optima of 3.0. The Lineweaver Burk analysis at various pH yielded pK(a) values of 3.3 and 4.29 indicating acidic amino acids at the active site of the enzyme. The structural changes exemplified compact secondary structure collapsed tertiary structure and exposure of hydrophobic patches at pH 10. The changes at pH 10 are typical of a molten globule state. This alkali induced molten globule is novel since acid induced molten globule state is more reported. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkali induced molten globule; Plant aspartic protease; Structural transitions

Production of single cell protein, essential amino acids, and xylanase by penicillium janthinellum - Rao, Mala; Varma, Anjanikumar; Deshmukh, Sumedha S. (Bioresources, 2010)
Microbial biomass having 46% crude protein content and enriched with essential amino acids as well as extracellular xylanase activity (100-150 IU/ml) was produced by an efficient fungal strain, Penicillium janthinellum (NCIM St-F-3b). Optimization studies for maximum xylanase and biomass production showed that the fungus required a simple medium containing bagasse hemicellulose as carbon source and ammonium sulphate as the nitrogen source. Therefore bagasse, which is a waste product of the sugar industry, can be efficiently used in microbioal biomass protein preparation for animal feed.
Keywords: Bagasse hydrolysate; Crude protein; Microbial biomass production; Penicillium janthinellum; Xylanase

Purification and characterization of an alkaline protease by a new strain of Beauveria sp - Shankar, Shiv; Rao, Mala; Laxman, Ryali Seeta (Process Biochemistry, 2011)
A fungal culture isolated from animal dung was identified as a new strain of Beauveria sp MTCC 5184 based on 18S rDNA and ITS nucleotide sequence homology. The fungal isolate secretes alkaline protease active at pH 9 and 50 degrees C. The alkaline protease from Beauveria sp (BAP) was purified to homogeneity with 10.2-folds increase in specific activity and 38.6% recovery. The molecular mass and isoelectric point of the protease were found to be 29 kDa and 9.3, respectively. The N-terminal sequence of the BAP showed only partial homology with subtilisin like proteases from other fungi. The enzyme was stable up to 40 degrees C and pH 3-11. The protease was inhibited by Cd(2+), Hg(2+) and Mn(2+). The activity was totally lost in the presence of 1 mM PMSF suggesting it to be a serine protease. The protease showed maximum activity with casein followed by haemoglobin and BSA. The purified protease is able to separate the endothelial cells and can be used in animal cell culture. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Animal cell culture; Beauveria sp; Sequence homology

Production, purification, and characterization of a beta-glucosidase of penicillium funiculosum NCL1 - Ramani, Gurusamy; Meera, Balasubramanian; Vanitha, Chinnathambi; Rao, Mala; Gunasekaran, Paramasamy (Applied Biochemistry and Biotechnology, 2012)
Penicillium funiculosum NCL1, a filamentous fungus, produced significantly higher levels of beta-glucosidase. The effect of initial pH, incubation temperature, and different carbon sources on extracellular beta-glucosidase production was studied in submerged fermentation. At 30 A degrees C with initial pH 5.0, enzyme production was increased by 48-fold upon induction with paper mill waste, as compared to commercial cellulose powder. In zymogram analysis, four isoforms of beta-glucosidases were observed with wheat bran whereas a minimum of one isoform was observed with other carbon sources. A major beta-glucosidase (Bgl3A) with the apparent molecular weight of similar to 120 kDa, induced by paper mill waste, was purified 19-fold to homogeneity, with a specific activity of 1,796 U/mg. Bgl3A was a monomeric glycoprotein with 29% of neutral carbohydrate content. It showed optimum activity at pH 4.0 and 5.0, optimum temperature at 60 A degrees C, and exhibited a half-life of 1 h at 60 A degrees C. K (m) of Bgl3A was found to be 0.057 mM with p-nitrophenyl beta-d-glucoside and V (max) was 1,920 U/mg. The purified enzyme exhibited glucose tolerance with a K (i) of 1.5 mM. Bgl3A readily hydrolyzed glucosides with beta-linkage. Bgl3A activity was enhanced (156%) by Zn2+ and was not affected by other metal cations and reagents. The supplementation of Bgl3A (5 U/mg) with Trichoderma reesei cellulase complex (5 FPU/mg) resulted in about 70% of enhanced glucose production, which emphasizes the industrial importance of Bgl3A.
Keywords: beta-Glucosidase; Paper mill waste; Penicillium funiculosum NCL1; Purification; Thermostability

Purification and biochemical characterization of endoglucanase from Penicillium pinophilum MS 20 - Pol, Dipali; Laxman, Ryali Seeta; Rao, Mala (Indian Journal of Biochemistry & Biophysics, 2012)
Cellulases find increasing prominence in sustainable production of fuel and feedstock from lignocellulosic biomass. The purification and biochemical characterization of individual components of cellulase complex is important to understand the mechanism of their action for the solubilization of crystalline cellulose. In this study, an extra-cellular endoglucanase isolated from culture filtrate of Penicillium pinophilum MS 20 was purified to homogeneity by ammonium sulphate precipitation, ion-exchange chromatography and gel filtration. The purified endoglucanase (specific activity 69 U/mg) was a monomeric protein with molecular mass of 42 kDa, as determined by SDS-PAGE. The endoglucanase was active over a broad range of pH (4-7) with maximum activity at pH 5 and showed optimum temperature of 50 degrees C. It retained 100% activity at 50 degrees C for 6 h and half- lives of 4 h and 3 h at 60 degrees C and 70 degrees C, respectively. The kinetic constants for the endoglucanase determined with carboxymethyl cellulose as substrate were V-max of 72.5 U/mg and apparent K-m of 4.8 mg/ml. The enzyme also showed moderate activity towards H3PO4 swollen cellulose and p-nitrophenyl beta-D-glucoside, but no activity towards filter paper, Avicel and oat spelt xylan. The activity was positively modulated by 47, 32 and 25% in the presence of Co2+, Zn2+ and Mg2+, respectively to the reaction mixture. The wide pH stability (4-7) and temperature stability up to 50 degrees C of endoglucanase makes the enzyme suitable for use in cellulose saccharification at moderate temperature and pH.
Keywords: Biochemical properties; Carboxymethyl cellulose; Endoglucanase; Penicillium pinophilum MS 20; Purification